PENGARUH PERSENTASE PEREKAT TAPIOKA TERHADAP KARAKTERISTIK BRIKET ARANG TEMPURUNG KELAPA - Norhikmah -; Noor Mirad Sari; Muhammad Faisal Mahdie (Jurnal Sylva Scienteae, 2021)
Tapioka flour as an adhesive for coconut shell charcoal briquettes can affect the characteristics of charcoal briquettes consisting of physical and chemical properties. The purpose of this study was to determine the physical properties of coconut shell charcoal briquettes in several adhesive percentages. The method used was a completely randomized design pattern and in this study there was only one factor (factor = coconut shell charcoal and tapioca adhesive/starch), as many as 5 treatments with 3 replicatins = 15 samples to be tested. Charakteristics of coconut shell charcoal briquettes that meet ASTM standard : water content that entered ASTM standard (Max 6%) in treatment A2 (95% coconut shell charcoal + 5% tapioca adhesive), the best density is found in treatment A3 (90% coconut shell charcoal + 10% tapioca adhesive)and enter ASTM standard(1.0-1.2 g / cm3), ash content that falls within the ASTM standard (Max 18%) in treatment A3(90% coconut shell charcoal + 10% tapioca adhesive), flying substancs that comply with ASTM standard (19-28%) in treatment A3 (90% charcoal coconut shell + 10% tapioca adhesive), bonded carbon content which is included in the ASTM standard (at least 58%) in treatment A2 (95% coconut shell charcoal + 5% tapioca adhesive),and the best heating value is found in the treatment A3 ( 90% coconut shell charcoal + 10% tapioca adhesive) which falls within the ASTM standard (4000-6500 cal / g). The results of this study indicate that the percentage of tapioca adhesive can affect the characteristics of coconut shell charcoal briquetess.Keywords: Percentage of tapioca adhesive; Charcoal briquettes; Coconut shell